Geography and modernity : changing land, law, and life on Cranborne Chase in the nineteenth century - Cheeseman, C (2007)
Cranborne Chase is distinctive not only for its predominantly rural landscape but also for its history as a hunting franchise. A vast expanse stretching into three counties - Dorset, Wiltshire, and Hampshire - it remained subject to premodern laws and land use patterns well into the modern period. This thesis sets out to examine the interaction and changing relationships between land, law, and life both immediately preceding and immediately following the Chase's 1830 disfranchisement, itself the culmination of a forty years' 'disfranchisement debate' between Lord Rivers and his neighbours, known collectively as 'the proprietors'. At the heart of the debate were two seemingly incompatible views of property, one distinctly premodern and the other distinctly modern, and yet with some interesting parallels. Lord Rivers sought to retain his franchise despite its being deemed an obstacle to innovation and improvement, a temptation towards crime, and a financial burden by the proprietors, whose own concerns were private profit and game preservation. His Lordship was keen to point out the social status and paternal feelings it engendered - its value was as much symbolic as financial - the local commoners being particular beneficiaries. In fact, in many ways, the preservation of deer promoted, rather than prevented, social unity and ecological stability. The Chase was not without its problems, though. Not only did the deer destroy certain crops and prevent the cultivation of others, but they were also much sought-after by generations of deer stealers, many of whom stole to supply a lucrative black market. Documents relating to numerous and often lengthy legal proceedings provide an abundance of information about the Chase's management and protection, as well as an insight into local criminal and social patterns. We will thus pursue three themes, or aspects, of the Chase's history, as well as their origins in, and implications for, its geography: firstly, land use and management; secondly, crime, particularly deer, game, and wood theft; and thirdly, hunting, including its cost, social significance, and modernisation. Many of these issues are discussed within their wider context, for although Cranborne Chase was in some ways very distinctive, it was also a prime example of national changes in law and lifestyle effecting local changes, with implications for both the land and its inhabitants.